Elaboração de indicadores de ciência e tecnologia para o monitoramento de avanços tecnológicos em nanocelulose - Milanez, Douglas Henrique (2015)
Nanocellulose is an economically promising nanomaterial that can be obtained from renewed sources. Due to its potential, it has been the subject of much research in Brazil and in the world. Nanocellulose is an emerging area and technological or regulatory changes may affect its business and research environment. Consequently, there is a high interest to follow its scientific and technological advances; however, there is a challenge to analyze the large volume of information available in scientific publication and patent documents. To deal with this task, besides the traditional data mining technique, text mining technique applied to patent claims has been developed, an area that can be considered a new frontier to develop Science and Technology indicators. This research aimed to investigate the development of useful indicators to monitor the technological advances in nanocellulose. It relied on data and text mining techniques applied to scientific publications, patent documents and patent claims. The results showed the resent increase on the number of publication and patents, highlighting nanocellulose as an important scientific and technological area for nanotechnology. Countries prioritized developments on microfibrillated cellulose, cellulose nanofibrils and nanocrystals. The patenting activity also indicated the potential value of these types of nanocellulose. The technological advances were concentrated on Macromolecular Chemistry and Materials Processing subdomains. Besides the cellulose, polymers from acrylic and vinyl classes accumulated more patents in technologies involving nanocellulose and composite materials. The claim indicators contributed to detail the content of patent documents in nanocellulose. The text mining methodology developed provided striking outcomes, especially in the characterization of important aspects of materials engineering associated with nanocelulose, a task difficult to be obtained from large volume of documents using other procedures.